Oral manifestation of ulcerative colitis - Đuričković Aleksa; Đuričković Mirjana (Serbian Medical Society - Dental Section, Belgrade, 2022)
Introduction Ulcerative colitis is an inflammatory bowel disease. Primary involvement is the colon. Changes in the oral cavity may occur as the part of extraintestinal manifestations of the disease. Most common are aphthous ulcers, angular cheilitis and pyostomatitis vegetans which is a specific marker of ulcerative colitis. Case report This case describes a 53-year-old patient who developed oral lesions as the part of ulcerative colitis. The patient was without symptoms of ulcerative colitis at the time of reporting to the dentist. After a few days, ulcerative colitis activated. Conclusion Changes that occur in the oral cavity may precede intestinal. It is very important that a dentist recognizes such changes and refers the patient to a gastroenterologist.